Stress and strain analysis in the rock massif during coal exploitation with large diameter boreholes in east field pit RMU Bogovina - Ivaz Jelena; Ignjatović Dragan; Ljubojev Milenko; Softić Sead (Mining and Metallurgy Engineering Bor, 2015)
This paper presents stress and strain analysis in massif during exploitation of out-of-balance coal layers in the BCM Bogovina. Behavior of the surrounding rock mass was tested during application of large diameter boreholes exploitation. Based on the proposed solutions for stope geometry and known geological conditions in deposit, physical and mechanical properties of coal and surrounding massif, the numerical analysis of the stress and strain of excavation area and surrounding massif was done. Numerical modeling of excavation area behavior was done using the software package Phase2, whose calculations are based on the finite element method. The analysis, conducted in this paper, has shown that there is a possibility for applying this kind of excavation in terms of stability the rock mass.